2014
DOI: 10.1159/000357798
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Disturbance in CADASIL: Its Impact on Quality of Life and Caregiver Burden

Abstract: Background and Purpose: Recurrent strokes and cognitive dysfunction are the major symptoms of cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL). However, emotional disturbances in CADASIL patients are incompletely understood. The aim of this study was to investigate emotional disturbances in CADASIL and their impact on the patients' quality of life (QOL) and caregiver burden. Methods: From 54 patients who were diagnosed as CADASIL between January 2000 and Augu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 70 publications
(44 reference statements)
0
23
0
Order By: Relevance
“…Third, this is the first study to investigate the relationship of considerable number of clinical variables with CMB in CADASIL patients. In the literature, only data about cognitive profile and some psychiatric disturbances are reported [ 23 , 28 , 31 , 32 ], but data are missing about many other clinical features typical of CADASIL. Fourth, our sample is composed of patients from different countries and this could make our results more generalizable to the CADASIL patient community.…”
Section: Discussionmentioning
confidence: 99%
“…Third, this is the first study to investigate the relationship of considerable number of clinical variables with CMB in CADASIL patients. In the literature, only data about cognitive profile and some psychiatric disturbances are reported [ 23 , 28 , 31 , 32 ], but data are missing about many other clinical features typical of CADASIL. Fourth, our sample is composed of patients from different countries and this could make our results more generalizable to the CADASIL patient community.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus unclear if the presence of CMBs is the independent predictor or rather severity of CSVD overall. In a special population of CADASIL, Park et al demonstrated that leukoaraiosis, not CMBs, is closely associated with depression ( 23 ), while Noh et al found depressive emotional disturbances was associated with multiple (≥10) CMBs, but not leukoaraiosis ( 24 ). Only a few studies adjusted the severity of leukoaraiosis in multivariate regression analyses ( 4 , 13 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with PSF are more often unemployed, change their jobs [ 12 , 13 ], and fail to return to previous jobs [ 13 - 16 ] than those without PSF. Although the overall negative impacts of PSEI and PSAP are less marked than those of PSD, they still lead to distress and embarrassment, impair certain domains of patients’ quality of life, and increase caregiver burden [ 17 ].…”
Section: Introductionmentioning
confidence: 99%